2009
DOI: 10.1021/jp908326y
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Crystalline Nematic Phase in Aqueous Suspensions of a Disk-Shaped Natural Beidellite Clay

Abstract: After size-selection and osmotic pressure measurements at fixed ionic strength, the behavior of aqueous colloidal suspensions of anisotropic disklike beidellite clay particles has been investigated by combining optical observations under polarized light, rheological, and small angle X-ray scattering (SAXS) experiments. The obtained phase diagrams (volume fraction/ionic strength) reveal, for ionic strength below 10(-3) M/L, a first-order isotropic/nematic (I/N) phase transition before gel formation at low volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
187
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(204 citation statements)
references
References 50 publications
16
187
0
1
Order By: Relevance
“…On increasing the concentration in water, this clay forms a birefringent nematic gel phase. 13 Under shear flow, for shear rates larger than 100 s -1 , the 2D SAXS patterns (figure 6) in the tangential geometry exhibit a strong anisotropy that is more and more pronounced upon increasing the shear rate up to 2000 s -1 . At the same time, in the radial geometry (figure 6), almost no anisotropy is observed.…”
Section: Doped Lamellar Phasesmentioning
confidence: 95%
“…On increasing the concentration in water, this clay forms a birefringent nematic gel phase. 13 Under shear flow, for shear rates larger than 100 s -1 , the 2D SAXS patterns (figure 6) in the tangential geometry exhibit a strong anisotropy that is more and more pronounced upon increasing the shear rate up to 2000 s -1 . At the same time, in the radial geometry (figure 6), almost no anisotropy is observed.…”
Section: Doped Lamellar Phasesmentioning
confidence: 95%
“…[19][20][21][22] Moreover, it has been found that suspensions of sodium montmorillonite and similar clays exhibit a negative (anomalous) birefringence, 14,23,24 sparking interest in the phenomenon. The mentioned anomaly consists in the tendency of the particles to orient under some conditions with their major axis perpendicular to the external field, instead of parallel, as in "normal" EB.…”
Section: Introductionmentioning
confidence: 99%
“…This effect was recently described in clay suspensions [47][48][49][50][51][52], in which the liquidcrystalline character is evidenced by polarised light microscopy and small-angle X-ray scattering. These experiments on clay-based gel samples reveal strong positional and orientation orders of the particles, proving unambiguously the nematic character of the clay mineral-rich gel.…”
Section: Discussionmentioning
confidence: 73%